I.Sicily as a Tool for the Study of Roman Sicily: An Experiment in Institutional Annotation - Prag, Jonathan; Tosques, Alfredo (Gerión. Revista de Historia Antigua, 2024)
Study of Roman Sicily is well established and has a long tradition, with the two most authoritative and well-established epigraphic corpora –CIL X (1883) and IG XIV (1890)– dating to the late 19th century. While I.Sicily was conceived to offer easy and up-to-date access to the evergrowing but increasingly scattered epigraphic evidence of Sicily, its digital nature also enables the adoption of new approaches and the pursuit of novel research questions. The open-access dataset has recently been expanded to include institutional annotations, which hold great promise for research, particularly in fields that rely on extensive and detailed datasets, such as administrative and onomastic history (prosopographic annotation will follow). This paper aims to demonstrate both the potential and the limitations of a digitally annotated dataset as a tool for historical research, through a preliminary case study on the practice of dedications to the Roman emperor in Sicily. Recent scholarship suggests that provincial subjects also contributed to shaping the notion and the expectations around emperorship, which were not only imposed from above. The data-driven approach facilitated by an annotated corpus is well-suited to the new bottom-up perspective, but it is not without methodological pitfalls, which will be highlighted in this paper.
Keywords: digital epigraphy; FAIR epigraphy; Digital Humanities; Roman emperor; Roman provinces